Effects of Cultivar Selection and Nitrogen Management on the Development and Productivity of Dual-Purposepearl Millet (Pennisetum glaucum L.): Optimizing Cultivar Selection and Nitrogen Management for Maximum Pearl Millet Yield (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The effects of cultivar selection and nitrogen management on the growth and production ofdual-purpose pearl millet (Pennisetum glaucum L.) are investigated in this research. The study examineshow various cultivars affect maturation length, forage quality, productivity potential, and resilience topests and diseases. It also examines how nitrogen management affects pasture quality, yieldimprovement, water usage efficiency, weed competition, and environmental impact. The resultsemphasize the need of selecting appropriate cultivars and putting into practice efficient nitrogenmanagement measures to maximize pearl millet yield. For farmers, agronomists, and academics engagedin the dual-purpose pearl millet production, the findings provide useful insights.